Analysis of radiological characteristics distribution in the vertebral bodies of the lumbosacral spine of competitive rowers - Ogurkowska, M. B. (Biology of Sport, 2010)
Unfavorable biomechanical situations, usually related to the performance of a profession and competitive sports practice, promote formation of overloads. This problem may be particularly perceptible among sportsmen that practice strength and stamina sports. The present study deals with rowing. The purpose of this study is to evaluate the degree of degenerative changes of the lumbosacral spine in competitive rowers, on the basis of an analysis of changes in the cancellous structure of vertebral bodies. This has been achieved on the basis of radiological density acquired from a CT test.